The Effect of Internet Development on Indonesia’s Agri-Food Export Potential in the Global Market - Suroso, Arif Imam; Fahmi, Idqan; Tandra, Hansen; Haryono, Adi (AGRARIS: Journal of Agribusiness and Rural Development Research, 2024)
The Internet has become essential in increasing output between corporate and country levels. However, the impact of the Internet on trading potential still needs to be known. On the other hand, Indonesia has great potential to export agricultural food products in global trade. Therefore, the relationship between the Internet development and agri-food export potential could be explored. This study aims to investigate the effect of Internet development on Indonesia’s export potential in the global market. The export potential estimation was measured using gravity estimation in 124 destination countries from 2010 to 2020. Furthermore, the panel regression was employed to determine the three indicators of Internet development: Internet users, secure Internet servers, and fixed broadband subscriptions on Indonesia’s agricultural export potential. This study also utilized simulation due to the possibility of rising the number of Internet indicators. The results revealed several positive factors of Indonesia’s agricultural exports, such as importers’ gross domestic bruto (GDP), contagious border, and colonial relationship. Otherwise, geographical distance, exchange rate, and being a landlocked country negatively affected Indonesia’s agricultural exports. Indonesia possessed a greater potential for agricultural exports in Europe, especially in the conditions of emerging and developing economies. There were 85 destination countries with higher potential for Indonesia’s agri-food export. Additionally, Internet users and secure Internet servers positively influenced the agricultural export potential to target countries. The simulation revealed that improving Internet indicators boosted the new market rather than raising the export value to target countries.